Spectroscopic investigation of N and Ne seeded induced detachment in JET ITER-like wall L-modes combining experiment and EDGE2D modeling. (August 2019) - Lomanowski, B.; Carr, M.; Field, A.; Groth, M.; Jaervinen, A.E.; Lowry, C.; Meigs, A.G.; Menmuir, S.; O'Mullane, M.; Reinke, M.L.; Stavrou, C.K.; Wiesen, S.; et al.
Highlights: N and Ne impurity seeding in JET-ILW L-mode plasmas leads to plasma detachment. The outer target ion flux reduction is due to a decrease in ionization source. Enhanced ionization at the outer target is caused by high Lyman series opacity. Edge plasma simulations without opacity show higher volume recombination. Abstract: Modeling and experimental investigation of the distribution of seeded impurities and their influence on divertor detachment in all-metal tokamaks is critical for developing reactor-scale exhaust scenarios. In this work, the degree and operating space for Ne and N impurity seeded induced detachment in JET with ITER-like wall (JET-ILW) L-mode discharges is shown to be regulated by the combination of i) the local radiative dissipation in the low-field side divertor; and ii) the incursion of the ionization front towards the X-point with increased impurity seeding. Using a quantitative spectroscopic approach, it is shown that the net particle balance at the low-field side target is dominated by a marked decrease in the ionization source between the X-point and the target with increased N and Ne seeding, and only a marginal increase in the volume recombination rate. With increased seeding, the local radiated power dissipation (N only) and reduction in the power crossing the separatrix (both nitrogen and neon) leads to a reduction in the low-field side target Te . Consequently, the incursion of the ionization front away from a region of enhanced ionization rate caused by high Lyman series opacity at the outer target leads to a steep decrease of the outer target ion flux. In contrast to experiment, EDGE2D-EIRENE simulations using optically thin divertor plasma assumptions show a larger impact of volume recombination and a factor of two shortfall in the low-field side divertor ne . A detailed assessment of opacity effects using the EIRENE photon transport module is recommended.